O celular e os novos modos de socialização - Vaz, Ana Carolina Rocha (2010)
The aim of this project is to identify and analyze the impacts of mobile telephone use in society. It was observed that use of this device can strengthen relationships through the exchange of information between users by means of photos, videos, text messages and phone calls. The mobile phone has proven to be a key element in ubiquitous computing and what differentiates it from other mobile devices is the fact that it can combine a number of features in one super-portable piece of equipment. Mobile phones are an efficient tool for coordinating activities. The possibility of rescheduling commitments in real-time, during breaks between one activity and another, can transform the experience of time according to researchers. The addition of localization systems to this device allowed new methods of appropriating physical space, especially in urban centers. The consequences of being available any time, any place, were also discussed. There are two movements going in opposite direction: although we have our entire social network available, at the same time, we become more vulnerable to those who wish to find us. This study is the result of reading the work of authors who analyzed the social changes occurring due to the advances in the development of smart technologies such as Pierre Levy and Manuel Castells. The issue of the impact caused by the use of mobile phones was discussed based on the research by Lucia Santaella, André Lemos, Adriana Souza e Silva, Richard Ling and Howard Rheingold